Knockdown of Ant2 Reduces Adipocyte Hypoxia And Improves Insulin Resistance in Obesity - Seo, Jong Bae (Nat Metab, 2018)
Decreased adipose tissue oxygen tension and increased HIF-1α expression can trigger adipose tissue inflammation and dysfunction in obesity. Our current understanding of obesity-associated decreased adipose tissue oxygen tension is mainly focused on changes in oxygen supply and angiogenesis. Here, we demonstrate that increased adipocyte O(2) demand, mediated by ANT2 activity, is the dominant cause of adipocyte hypoxia. Deletion of adipocyte Ant2 improves obesity-induced intracellular adipocyte hypoxia by decreasing obesity-induced adipocyte oxygen demand, without effects on mitochondrial number or mass, or oligomycin-sensitive respiration. This led to decreased adipose tissue HIF-1α expression and inflammation with improved glucose tolerance and insulin resistance in both a preventative or therapeutic setting. Our results suggest that ANT2 may be a target for the development of insulin sensitizing drugs and that ANT2 inhibition might have clinical utility.